FUNCTIONALITY OF LEGAL REGULATION IN THE FIELD OF AIR TRANSPORT - Полянська, Анна Євгенівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
The aim: to study the state regulation of air transport, the formation of state policy and strategy for the development of air transport. Research methodology is based on the methods of documentary analysis and synthesis, comparative analysis, objective truth, which allowed to systematically trace the impact of legal regulation in the field of air transport. The results: it was stated, that the legal system is an important component in the management of air transport. With proper legal regulation, there will be a rapid development of air transport. The discussion: state policy in the field of air transport is a set of goals, objectives, priorities, principles, strategic programs and planning measures, which are developed and implemented by public authorities, which allows the state to achieve the agreed goals in the aviation industry, using legal, economic, administrative and other methods and means of influence, based on the resources at its disposal. The peculiarity of this state policy is that, first, it is closely related to both foreign and domestic processes in the country; secondly, has a great influence on the development of all socio-economic relations; thirdly, it is provided by a system of public administration bodies headed by the head of state; fourth, it is quite dynamic and costly; fifth, it needs constant control and adjustment by the state. State regulation of air transport is the formation of state policy and development strategy, defining tasks, functions, conditions of activity in the field of aviation and use of Ukrainian airspace, application of aviation security measures, adoption of mandatory aviation rules of Ukraine, state control over their implementation and establishing responsibility for their violation.